A newly observed physical cause of the onset of the subsurface spring phytoplankton bloom in the southwestern East Sea/Sea of Japan - Y.-T. Son (Biogeosciences, 2014)
An ocean buoy, UBIM (Ulleung Basin Integrated Mooring), deployed during the spring transition from February to May 2010 reveals for the first time highly resolved temporal variation of biochemical properties of the upper layer of the Ulleung Basin in the southwestern East Sea/Sea of Japan. The time-series measurement captured the onset of subsurface spring bloom at 30 m, and collocated temperature and current data gives an insight into a mechanism that triggers the onset of the spring bloom not documented so far. Low-frequency modulation of the mixed layer depth ranging from 10 m to 53 m during the entire mooring period is mainly determined by shoaling and deepening of isothermal depths depending on the placement of UBIM on the cold or warm side of the frontal jet. The occurrence of the spring bloom at 30 m is concomitant with the appearance of colder East Sea Intermediate Water at buoy UBIM, which results in subsurface cooling and shoaling of isotherms to the shallower depth levels during the bloom period than those that occurred during the pre-bloom period. Isolines of temperature-based NO3 are also shown to be uplifted during the bloom period. It is suggested that the springtime spreading of the East Sea Intermediate Water is one of the important factors that triggers the subsurface spring bloom below the mixed layer.